Aetiology of pyrexia of unknown origin in north India. (January 2021) - Pannu, Ashok Kumar; Golla, Rithvik; Kumari, Savita; Suri, Vikas; Gupta, Pankaj; Kumar, Rajender
The aetiology of pyrexia of unknown origin (PUO) varies dramatically according to epidemiology. We studied the cause and spectrum of PUO in Indian adults. A total of 152 patients (112 prospectively and 40 retrospectively) met Petersdorf and Beeson's criteria. The diagnostic evaluation was guided by potentially diagnostic clues, based on a 'step-wise' approach. The five main categories, i.e. infectious, neoplastic, non-infectious inflammatory, miscellaneous and undiagnosed comprised 43.4%, 21.5%, 19.7%, 2.0% and 12.5%, respectively. The top three causes were tuberculosis (n = 43, 28.3%), lymphoma (n = 19, 12.5%) and adult-onset Still's disease (n = 12, 7.9%). Tuberculosis predominated in all age groups, and about 70% of cases had the extrapulmonary form, the most common being gastrointestinal. Hodgkin and non-Hodgkin lymphomas were equally distributed, but solid malignancies were uncommon. Adult-onset Still's disease was the second commonest cause in adults aged ≤ 40 years. Fever resolved spontaneously in 12/19 cases of undiagnosed cause. Extrapulmonary tuberculosis remains the most prevalent PUO in India.